Soybean F-Box-Like Protein GmFBL144 Interacts With Small Heat Shock Protein and Negatively Regulates Plant Drought Stress Tolerance - Xu, Keheng; Zhao, Yu; Zhao, Yan; Feng, Chen; Zhang, Yinhe; Wang, Fawei; Li, Xiaowei; Gao, Hongtao; Liu, Weican; Jing, Yan; Saxena, Rachit K.; Feng, Xianzhong; et al. (Frontiers in Plant Science, 2022)
Abstract The F-box gene family is one of the largest gene families in plants. These genes regulate plant growth and development, as well as biotic and abiotic stress responses, and they have been extensively researched. Drought stress is one of the major factors limiting the yield and quality of soybean. In this study, bioinformatics analysis of the soybean F-box gene family was performed, and the role of soybean F-box-like gene GmFBL144 in drought stress adaptation was characterized. We identified 507 F-box genes in the soybean genome database, which were classified into 11 subfamilies. The expression profiles showed that GmFBL144 was highly expressed in plant roots. Overexpression of GmFBL144 increased the sensitivity of transgenic Arabidopsis to drought stress. Under drought stress, the hydrogen peroxide (H2O2) and malonaldehyde (MDA) contents of transgenic Arabidopsis were higher than those of the wild type (WT) and empty vector control, and the chlorophyll content was lower than that of the control. Y2H and bimolecular fluorescence complementation (BiFC) assays showed that GmFBL144 can interact with GmsHSP. Furthermore, our results showed that GmFBL144 can form SCFFBL144 (E3 ubiquitin ligase) with GmSkp1 and GmCullin1. Altogether, these results indicate that the soybean F-box-like protein GmFBL144 may negatively regulate plant drought stress tolerance by interacting with sHSP. These findings provide a basis for molecular genetics and breeding of soybean.